ANALISIS FRAUD TRIANGLE PADA TINDAK PIDANA KORUPSI BERBASIS DIGITAL (STUDI KASUS PROYEK BTS 4G KOMINFO) - Tri Anindya Febriani; Aisyah Nurul Ikhsani; Putri Rahmawati; Hastanti Agustin Rahayu (Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the application of Fraud Triangle theory in explaining the factors behind digital-based corruption in the BTS 4G Kominfo Project. The research employs a qualitative approach with a descriptive case study method using secondary data obtained from official government reports, legal documents, credible online news, and relevant academic literature. Data analysis was conducted through reduction and thematic interpretation based on the three main elements of the Fraud Triangle: pressure, opportunity, and rationalization. The results show that political pressure and bureaucratic targets created a strong motivation for administrative manipulation, while weak digital oversight systems provided significant opportunities for fraud. Furthermore, perpetrators tended to rationalize their actions as a form of efficiency for project continuity. These findings emphasize the importance of integrating digital supervision and strengthening public officials’ ethics to prevent fraud in the government sector.